Biochemical and cell biological analysis of actin in the nematode Caenorhabditis elegans - Ono, Shoichiro (2011)
The nematode Caenorhabditis elegans has long been a useful model organism for muscle research. Its body wall muscle is obliquely striated muscle and exhibits structural similarities with vertebrate striated muscle. Actin is the core component of the muscle thin filaments, which are highly ordered in sarcomeric structures in striated muscle. Genetic studies have identified genes that regulate proper organization and function of actin filaments in C. elegans muscle, and sequence of the worm genome has revealed a number of conserved candidate genes that may regulate actin. To precisely understand the functions of actin-binding proteins, such genetic and genomic studies need to be complemented by biochemical characterization of these actin-binding proteins in vitro. This article describes methods for purification and biochemical characterization of actin from C. elegans. Although rabbit muscle actin is commonly used to characterize actin-binding proteins from many eukaryotic organisms, we detect several quantitative differences between C. elegans actin and rabbit muscle actin, highlighting that use of actin from an appropriate source is important in some cases. Additionally, we describe probes for cell biological analysis of actin in C. elegans.